Homozygous Germline APC p.I1307K Variants: A Case Series - Alexa Rosenblum; Michelle Springer; Amanda Eppolito; Lisen Axell; Lisa Mohler (Case Reports in Oncology, 2021)
Approximately 10% of all colorectal cancer is estimated to be due to an inherited predisposition. Identification of a germline pathogenic variant can aid in treatment, screening, and surveillance and help stratify familial cancer risks based on gene-specific cancer associations. The APC gene contributes to a small percentage of hereditary colon cancer, with most pathogenic APC variants causing familial adenomatous polyposis syndrome. However, one specific variant in APC called p.I1307K, found in approximately 10% of Ashkenazi Jewish individuals, is associated with a moderate risk for colon cancer, but not polyposis. Heterozygous carriers of one p.I1307K variant are well documented in the literature, and guidelines recommend earlier and more frequent colonoscopies. Conversely, reports of homozygous carriers of 2 p.I1307K variants are limited, and guidelines for medical management are lacking. This case series describes 4 homozygous p.I1307K patients of Ashkenazi Jewish ancestry identified in cancer genetics clinics. Case 1 is a 73-year-old pancreatic cancer patient with a family history of melanoma and colon cancer. Case 2 is a 62-year-old patient with a personal history of 4 adenomatous colorectal polyps and a family history of breast, pancreatic, colon, and prostate cancers. Case 3 is a 52-year-old patient with a personal history of early-onset breast cancer and uveal melanoma and a family history of breast, prostate, and stomach cancers. Case 4 is a 70-year-old patient with a personal history of gallbladder adenocarcinoma and a family history of breast cancer. These cases exhibit wide phenotypic variability and contribute to the limited reports of homozygous p.I1307K variant carriers.